(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
لقد أظهرت نتائج تحليل 22عينة من بذور البطيخ الأحمر الكاملة, أنّها تحتوي على اللبّ 45.6 ±0.56% والزيت 20.83 ±0.76%, والبروتين 22 ± 0.44% والرماد 2.5±0.17% والألياف38.42± 0.27% والكربوهيدرات 10.4±0.53%.كما أظهرت النتائج أنّ العناصر المعدنية الرئيسة في لب البذور هي:الكالسيوم ( 130 ±8.4) والبوتاسيوم( 640 ±13.3) والفوسفور( 1031 ±15.7) والمغنيزيوم( 357 ±12.8) والحديد (12.6 ±1.8) ملغ /100غ. كما أوضحت نتائج تحليل الليبيدات أنّ معامل الانكسار 1.4747 ± 0.0004 ورقم التصبن190.6±4.25 والرقم اليودي123.23±3.43 ونسبة الفوسفولبيدات 1.2± 0.17% فيها. وقد أظهرت نتائج التحليل الكروماتوغرافي للأحماض الدهنية أنّ الزيت يحتوي على 20,25% أحماضاً دهنية مشبعة (البالميتيك 11.8± 0.25%, ويليه حمض الستياريك 7.5± 0.52%, ثم حمض اللوريك والميريستيك والأراكيديك بنسب صغيرة تقل عن 1% لكل منها), و79,75% أحماضاً دهنية غيرمشبعة( اللينولييك هو الحمض الرئيس في جميع العينات 63.4± 0.91%, ويليه الأولييك15.9± 0.61%, ثم اللينولينيك والبالميتولييك والجادولييك بمتوسط يقل عن 1% لكلّ منها) من مجموع الأحماض الدهنية. The chemical composition of twenty two samples of watermelon seeds and oil is studied. The results show that the seeds contain 45,6±0.56% kernel, 22±044%protein, 20.8 ±076% oil, 38.4±027% fibers,10,4±0.53 carbohydrates, and 2.5±0.17% ash. Mineral analysis of the kernels has given the following results (mg/100g): Ca,130±8.4, K,640±13.3, P,1031±15.7, Mg, 357±12.8 and Fe,12.6±1.8. The results of lipid analysis show that the phospholipids content is 1.2±0.17%, saponifiction value 190.6±4.25, iodine value 123±3.43, and refraction index 1.4747. Chromatographic analysis of the oil fat acids demonstrate the presence of 20% of saturated fat acids, namely Palmitic(11.8±0.25%) and Stearic(7.5±0.52%), as well as traces (less than1%each) of Lauric, Myristic and Arachidic acids. Unsaturated fat acids content has been 79.75%, of which Linoleic has been the main fat acid (63.4±0.91%).The other acids, namely Oleic(15.9±0.61%), Linolenic, Palmitoleic and Gadoleic have been (less than 1% each).